Early Exposure to Cardiac Treatment and Distress Among Patients and Their Caregiving Partners - Cornelius, Talea; Vilchinsky, Noa; Fait, Keren; Matetzky, Shlomi; Hod, Hanoch (Frontiers in Psychology, 2020)
Background. The experience of an acute coronary event (ACE), including early care and evaluation, can be a distressing and traumatic experience for patients and their romantic partners, who also act as caregivers. We hypothesized that, among partners who were present during the ACE, those who were also present during (1) transportation to the hospital and (2) initial medical treatment would experience greater (a) anxiety early post-event and (b) posttraumatic stress symptoms (PSS) related to the event four months later. The associations between partner presence with patient anxiety and PSS were also explored. Methods. Participants were ACE patients and their partners recruited between March 2015 and December 2016 from the Intensive Cardiac Care Unit (ICCU) of the Sheba Medical Center in Israel (N = 143; all patients were males and partners were females). Partners self-reported whether or not they were present during the cardiac event, the hospital drive, and initial care. Patients and partners self-reported anxiety in-hospital and PSS, keyed to the ACE, an average of four months later. Data were analyzed using General Estimating Equations (GEE) and Multilevel Modeling. Results. Neither patient anxiety nor PSS differed according to partner presence during the drive to the hospital. In contrast, partners had higher anxiety when they were not present at all (difference = 3.65, p = .019) and when present during the event and during the drive (difference = 2.93, p = .029) as compared to when they were present for the event but not for the drive. Partners who were present during the event, but not the drive, had lower PSS than those who were present for both the event and the drive (difference = -4.64, p = .026). Conclusions. Partners who accompany patients on the drive to the hospital may inadvertently put themselves at risk for greater distress following their loved one’s cardiac event. Future research should enrol couples in an acute care context to inform couple-targeted tailored interventions to reduce distress in patients and their caregiving partners.